Evaluation of serum cathepsin B, D, and L concentrations in women with late-onset preeclampsia - ANIK İLHAN, GÖKÇE (GALENOS YAYINCILIK, 2019)
Objective: The aim of the study was to assess serum cathepsin B, D, and L concentrations in women with late-onset preeclampsia. Materials and Methods: One hundred forty pregnant women were enrolled in the study, of which 100 subjects were preeclamptic and 40 were healthy controls. Serum concentrations of cathepsin B, D, and L were measured and compared between the preeclamptic and control groups. Results: Cathepsin B and D concentrations were significantly higher in the preeclamptic group compared with the control group. There was no statistically significant difference between the groups in terms of cathepsin L concentrations. Cathepsin B concentrations were significantly higher in women with preeclampsia with severe features compared with those with preeclampsia alone. Conclusion: Women with late-onset preeclampsia have significantly higher serum cathepsin B and D concentrations than controls. Cathepsin B and D may be promising biomarkers in women with late-onset preeclampsia.
Keywords: Cathepsin B; cathepsin D; cathepsin L; preeclampsia; CYSTEINE CATHEPSINS; PROTEASES